The Effect of Deep Learning Approach on Conceptual Understanding and Critical Reasoning among Vocational High School Students - Syamsiah, Siti Nurul; Wawan, Wawan; Anwar, Muhammad Saidun; Setiawan, Agus; Choirudin, Choirudin (Jurnal Pendidikan Matematika, 2026)
This study was motivated by the low conceptual understanding and critical mathematical reasoning among vocational high school students, largely due to conventional instruction emphasizing procedural memorization, and the limited empirical evidence on deep learning interventions in vocational mathematics. This investigation aimed to examine the effect of the deep learning approach on vocational students' conceptual understanding and critical mathematical reasoning regarding exponential functions. A quasi-experimental posttest-only non-equivalent control group design was implemented. The sample comprised 40 tenth-grade students from SMK Ma'arif 1 Metro, assigned to an experimental group (n=19) receiving deep learning instruction and a control group (n=21) receiving conventional instruction. Data were collected using conceptual understanding and critical reasoning tests (10 multiple-choice items each), validated by four experts using Aiken's V (mean V=0.76, high; mean V=0.67, moderate), with reliability (Spearman-Brown=0.730). Data were analyzed using Multivariate Analysis of Variance (MANOVA). The findings revealed a statistically significant multivariate difference between groups (Wilks' Λ=0.519; F=17.123; p<0.05; partial η²=0.481). Univariate analyses confirmed significantly higher conceptual understanding (F=7.634; p<0.05; partial η²=0.167) and critical reasoning (F=18.937; p<0.001; partial η²=0.333) in the deep learning class. These findings suggest that deep learning pedagogy may foster vocational students' higher-order cognitive skills, encouraging mathematics educators to integrate mindful, meaningful, and joyful learning activities connected to industrial contexts. Penelitian ini dilatarbelakangi oleh rendahnya pemahaman konsep dan penalaran kritis matematis siswa SMK yang disebabkan oleh pembelajaran konvensional yang berorientasi pada hafalan prosedural, serta terbatasnya bukti empiris tentang intervensi deep learning dalam matematika vokasi. Penelitian ini bertujuan menganalisis pengaruh pendekatan deep learning terhadap pemahaman konsep dan penalaran kritis matematis siswa SMK pada materi eksponen. Metode kuasi-eksperimen dengan desain posttest-only non-equivalent control group digunakan. Sampel terdiri dari 40 siswa kelas X SMK Ma'arif 1 Metro, terbagi dalam kelompok eksperimen (n=19) yang mendapat pembelajaran deep learning dan kelompok kontrol (n=21) dengan pembelajaran konvensional. Data dikumpulkan menggunakan tes pemahaman konsep dan penalaran kritis (masing-masing 10 soal pilihan ganda), divalidasi oleh empat ahli menggunakan Aiken's V (rata-rata V=0,76 kategori tinggi; V=0,67 kategori sedang), dengan reliabilitas Spearman-Brown 0,730. Analisis data menggunakan MANOVA. Hasil penelitian menunjukkan perbedaan multivariat signifikan antara kedua kelompok (Wilks' Λ=0,519; F=17,123; p<0,05; partial η²=0,481). Analisis univariat mengonfirmasi bahwa kelas deep learning memiliki pemahaman konsep (F=7,634; p<0,05; partial η²=0,167) dan penalaran kritis (F=18,937; p<0,001; partial η²=0,333) yang lebih tinggi secara signifikan. Temuan ini mengindikasikan bahwa pendekatan deep learning berpotensi mengembangkan kemampuan berpikir tingkat tinggi siswa SMK, sehingga mendorong pendidik matematika untuk mengintegrasikan aktivitas pembelajaran mindful, meaningful, dan joyful yang terhubung dengan konteks industri.